2010
DOI: 10.1021/ja1014103
|View full text |Cite
|
Sign up to set email alerts
|

A Palette of Fluorescent Probes with Varying Emission Colors for Imaging Hydrogen Peroxide Signaling in Living Cells

Abstract: We present a new family of fluorescent probes with varying emission colors for selectively imaging hydrogen peroxide (H 2 O 2 ) generated at physiological cell signaling levels. This structurally homologous series of fluorescein-and rhodol-based reporters relies on a chemospecific boronate-tophenol switch to respond to H 2 O 2 over a panel of biologically relevant reactive oxygen species (ROS) with tunable excitation and emission maxima and sensitivity to endogenously produced H 2 O 2 signals, as shown by stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
346
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 488 publications
(371 citation statements)
references
References 104 publications
13
346
0
3
Order By: Relevance
“…Our data provide the missing link between agonist-evoked calcium signals and ROS production, which were previously described to be connected in epidermal cell lines (9). EGF-induced H 2 O 2 production by A431 cells was originally described by Bae et al (8) and was subsequently confirmed by several other groups (22), (23). In a recent work, the phagocytic NADPH oxidase, Nox2 was detected in A431 cells, however no attempt was made to establish a correlation between ROS production and Nox2 expression (24).…”
Section: Discussionsupporting
confidence: 69%
“…Our data provide the missing link between agonist-evoked calcium signals and ROS production, which were previously described to be connected in epidermal cell lines (9). EGF-induced H 2 O 2 production by A431 cells was originally described by Bae et al (8) and was subsequently confirmed by several other groups (22), (23). In a recent work, the phagocytic NADPH oxidase, Nox2 was detected in A431 cells, however no attempt was made to establish a correlation between ROS production and Nox2 expression (24).…”
Section: Discussionsupporting
confidence: 69%
“…Accordingly, we developed a unique H 2 O 2 -specific fluorescent indicator, PY1-ME (Fig. S1A), which combines a boronate-masked phenol for the selective detection of H 2 O 2 (10,(33)(34)(35)(36)(37)(38)(39) and an appended methyl-ester group designed to increase cellular uptake and retention upon cleavage by intracellular esterases; this latter feature makes the dye suitable for both fluorescence imaging and flow cytometry experiments. Because this probe relies on a specific molecular reaction between H 2 O 2 and the boronate to generate a fluorescence signal, rather than thiol-based chemistry that can occur by non-specific ROS oxidation or disulfide exchange, our chemical method affords a direct measure of H 2 O 2 in cellular specimens.…”
Section: Resultsmentioning
confidence: 99%
“…3 Thus, for a long period of time, the carboxylic group was considered to be indispensable for strong fluorescence and was included in almost all fluorescein-based fluorescence probes. [4][5][6][7][8][9][10][11] Recently, T. Nagano et al [12][13][14][15][16][17] proposed that the fluorescein molecule can be regarded as a directly linked donoracceptor system, where the benzene moiety and the xanthene moiety were the electron donor and acceptor, respectively. The fluorescence quantum yield (F fl ) of fluorescein is dependent on photoinduced electron transfer (PeT) from donor to acceptor.…”
Section: Introductionmentioning
confidence: 99%